Response of Banana to Drip Irrigation and Mulching in Coastal Orissa - Paul, J C; Mishra, J N; Pradhan, P L (Journal of Agricultural Engineering, 2008)
Field experiments were conducted on loamy sand soil in coastal Orissa for two consecutive years (2006-08) to evaluate the economic feasibility of drip irrigation with black LLDPE mulch in banana crop. The net average seasonal water requirement of the crop was estimated to be 997 mm. The effect of three irrigation levels viz. net irrigation volume (V), 0.8 V and 0.6 V with drip in conjunction with black LLDPE mulch were studied on biometric and yield response of banana crop. The results of ring basin surface irrigation either alone or in conjunction with black LLDPE mulch were compared with drip irrigation. The study indicated better plant growth, early flowering, more number of fingers and enhancement in the yield under drip irrigation with plastic mulch. The highest yield (70.97 t/ha) was recorded under 0.8 V drip imgation with mulch as compared to other treatments. An increase of 33 % in yield, 49 % in net seasonal income and highest benefit-cost ratio (2.24) were recorded in case of 0.8 V drip imgation with mulch as compared to conventional ring basin irrigation. Mulch alone could increase the yield by 7% even in the absence of drip. The water requirement and seasonal cost of cultivation of the 2nd year banana crop (1st ratoon) was also less than the 1st year banana crop (fresh crop), because the suckers of ratoon crop was allowed 3 to 4 months along with the main crop in the field. Hence, there was a net saving of 4 months after harvest of the ratoon crop.